Economic burden of sickle cell disease in Sweden: a population-based national register study with 13 years follow up - Kjellander, Christian; Hernlund, Emma; Ivergård, Moa; Svedbom, Axel; Dibbern, Therese; Stenling, Anna; Sjöö, Fredrik; Vertuani, Simona; Glenthøj, Andreas; Cherif, Honar (Frontiers in Hematology, 2023)
INTRODUCTION: Sickle cell disease (SCD) describes a group of inherited disorders of hemoglobin. Globally, SCD occurs in approximately 300,000-400,000 births annually and is most prevalent in malaria-endemic countries. However, migration has impacted the epidemiology of SCD but data on the matter are scarce. The objective of this study was to describe the epidemiology, treatment uptake, and economic burden of SCD in Sweden, a country with substantial immigration over the last decades. METHODS: This nationwide retrospective observational registry cohort study identified patients with SCD from 2001 to 2018 and followed them from 2006 to 2018. Using data from high-quality population-based Swedish registers, we estimated prevalence, treatment uptake, and SCD-related health care resource use, sick leave and disability pension. RESULTS: Between 2006 and 2018 the number of patients with SCD increased from 504 to 670; inpatient hospital stays and outpatient visits increased by 200% and 300%, respectively. Patients with pain crises had approximately twice the number of inpatient episodes and outpatient visit per year, and had higher productivity losses compared to patients without crises. CONCLUSIONS: In an era of emerging treatments for SCD, we have, to the best of our knowledge, for the first time comprehensively described epidemiological and economic aspects of SCD in a country where the disease is still rare and not well recognised by the healthcare system.